Environmental sensing by African trypanosomes. (August 2016) - Roditi, Isabel; Schumann, Gabriela; Naguleswaran, Arunasalam
Highlights: Trypanosomes can perceive host serum components and modulate receptor expression. Multiple repressors and activators fine-tune responses to differentiation signals. Environmental factors regulate mRNA stability and nutrient uptake. Heat shock responses are mediated by RNA-binding and chromatin-binding proteins. Procyclic forms release and react to factors that orchestrate social behavior. Abstract : African trypanosomes, which divide their life cycle between mammals and tsetse flies, are confronted with environments that differ widely in temperature, nutrient availability and host responses to infection. In particular, since trypanosomes cannot predict when they will be transmitted between hosts, it is vital for them to be able to sense and adapt to their milieu. Thanks to technical advances, significant progress has been made in understanding how the parasites perceive external stimuli and react to them. There is also a growing awareness that trypanosomes use a variety of mechanisms to exchange information with each other, thereby enhancing their chances of survival.